Fisheries in Norway and Iceland: A comparative study - Tobias Holmeset 1988- (2023)
Iceland and Norway are two countries with shared historical and cultural heritage. They are both today considered to be two of the most important fisheries nations in the developed world. Even though these two nations have strong ties regarding history, culture, fisheries management, technological development, and production, there are still considerable differences. Some of the differences can be explained by biological, geographical, and oceanographic reasons, while others can be directed to political, economic, and social causes. The purpose of this thesis is to study how these two nations implemented modern fisheries management regarding the catch of demersal whitefish, primarily Atlantic cod, saithe and haddock, to deal with unprofitability and overcapacity in the past. And further, how the different paths chosen by these nations affect the fishing activity differently regarding profitability, fleet structure, fishing equipment, processing technology, exports, and demographic impacts. The main research question to be answered is how the differences in the restructured fisheries management system has led to differences that can be seen on the overall output of the fishing activity in the aspects mentioned above. The reasons why these differences have occurred will be traced and the consequences of the different paths that these nations have chosen will be presented and discussed. The conclusion to this question is that Norway and Iceland have chosen different paths in its modern fisheries management to deal with the same problems of unprofitability and overcapacity. The consequences of the different paths and regulations that are chosen may be traced in all aspects of the fishing activity.